Oxidative Stress in Seminal Plasma Negatively Influences Sperm Quality in Infertile Males - Mahat, Roshan Kumar; Bhale, Dhananjay Vasantrao; Rathore, Vedika (Faculty of Medicine Universitas Padjadjaran, 2023)
Objective: To investigate the association between malondialdehyde concentration in the seminal plasma of infertile men and sperm quality.Methods: This case-control study included 60 male participants ranging from 25-40 years old with half of them were fertile and the other half were infertile. Semen analysis was performed as per the WHO standards, and spectrophotometric measurement of seminal plasma malondialdehyde level was done.Results: Results showed that infertile men had significantly a higher mean level of malondialdehyde in their seminal plasma than fertile men (p<0.001), which was inversely associated with sperm count and motility. Also, malondialdehyde was positively associated with abnormal sperm morphology.Conclusions: Elevated malondialdehyde levels in seminal plasma are associated with poor sperm quality. Malondialdehyde testing can, therefore, be used to diagnose and predict the outcome of male infertility. Antioxidants should also be administered to men with infertility to help counteract the effects of oxidative stress.